Agroforestry adoption studies about farmer’s decision making on tree planting have been conducted for many cases, but there was an important aspect that still had less concern about farmer views especially how they choose the plant species and planting pattern and why they do that. The aim of this study was to explain the farmer’s reasons when they choose a plant species and planting pattern with different land tenure systems, state forest and private land. Method used in this study was a case - Indra G. Febryano; Didik Suharjito; Sudarsono Soedomo (Forum Pasca Sarjana, 2009)
Agroforestry adoption studies about farmer’s decision making on tree planting have been conducted for many cases, but there was an important aspect that still had less concern about farmer views especially how they choose the plant species and planting pattern and why they do that. The aim of this study was to explain the farmer’s reasons when they choose a plant species and planting pattern with different land tenure systems, state forest and private land. Method used in this study was a case study through analyzing plant species and planting pattern selection, financial flow, and household revenue structure. The results showed that: the farmer’s reasons were (1) cash income, (2) production continuity, (3) gestation period, (4) easy maintenance and harvest, (5) easy post harvest process, (6) tolerance to be planted with other plants, and (7) land tenure security (especially in state forest land); most farmers chose cacao species, with the main combination of planting patterns that consist of cacao and banana in state forest land, cacao and petai, cacao and durian in private land; and all the planting pattern were financially feasible; the largest contribution was given by cacao at all planting patterns based on farmer household revenue structure. Keywords: farmer’s decision making, crop and planting pattern selection, agroforestry